Unrecognized controls on microbial functioning in Blue Carbon ecosystems: The role of mineral enzyme stabilization and allochthonous substrate supply. Issue 2 (7th January 2020) - Mueller, Peter; Granse, Dirk; Nolte, Stefanie; Weingartner, Magdalena; Hoth, Stefan; Jensen, Kai
Abstract: Tidal wetlands are effective carbon sinks, mitigating climate change through the long‐term removal of atmospheric CO2 . Studies along surface‐elevation and thus flooding‐frequency gradients in tidal wetlands are often used to understand the effects of accelerated sea‐level rise on carbon sequestration, a process that is primarily determined by the balance of primary production and microbial decomposition. It has often been hypothesized that rates of microbial decomposition would increase with elevation and associated increases in soil oxygen availability; however, previous studies yield a wide range of outcomes and equivocal results. Our mechanistic understanding of the elevation–decomposition relationship is limited because most effort has been devoted to understanding the terminal steps of the decomposition process. A few studies assessed microbial exo‐enzyme activities (EEAs) as initial and rate‐limiting steps that often reveal important insight into microbial energy and nutrient constraints. The present study assessed EEAs and microbial abundance along a coastal ecotone stretching a flooding gradient from tidal flat to high marsh in the European Wadden Sea. We found that stabilization of exo‐enzymes to mineral sediments leads to high specific EEAs at low substrate concentrations in frequently flooded, sediment‐rich zones of the studied ecotone. We argue that the high background activity of a mineral‐associated enzyme pool provides a stable decomposition matrix in highly dynamic, frequently flooded zones. Furthermore, we demonstrate that microbial communities are less nutrient limited in frequently flooded zones, where inputs of nutrient‐rich marine organic matter are higher. This was reflected in both increasing exo‐enzymatic carbon versus nutrient acquisition and decreasing fungal versus bacterial abundance with increasing flooding frequency. Our findings thereby suggest two previously unrecognized mechanisms that may contribute to stimulated microbial activity despite decreasing oxygen availability in response to accelerated sea‐level rise. Abstract : The present study assessed exo‐enyzme activities (EEAs) and microbial abundance along a coastal ecotone stretching a flooding gradient from tidal flat to high marsh. We found that stabilization of exo‐enzymes to mineral sediments leads to high specific EEAs at low substrate concentrations in frequently flooded, sediment‐rich zones of the studied ecotone. Furthermore, we demonstrate that microbial communities are less nutrient limited in frequently flooded zones, where inputs of nutrient‐rich marine organic matter are higher. This was reflected in both increasing exo‐enzymatic carbon versus nutrient acquisition and decreasing fungal versus bacterial abundance with increasing flooding frequency.